2021
DOI: 10.22541/au.162276602.20240137/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Primary Breast Osteosarcoma; a case report and review of the literature

Abstract: Primary breast osteosarcoma (PBOS) is an extremely rare and poor prognostic malignancy that has not a definitive treatment guideline. Here we presented a successfully treated case of PBOS and provided a comprehensive review of the literature which revealed the divergence of opinions regarding the histogenesis and management of this malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The origin of the tumor is uncertain. Researchers approach this tumor similar to a sarcoma (cells originated from totipotent mesenchymal cells of the mammary gland or mesodermal remnants), while Emad A. Rakha showed that almost all POBS are derived from an epithelial origin after being under metaplastic transformation ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…The origin of the tumor is uncertain. Researchers approach this tumor similar to a sarcoma (cells originated from totipotent mesenchymal cells of the mammary gland or mesodermal remnants), while Emad A. Rakha showed that almost all POBS are derived from an epithelial origin after being under metaplastic transformation ( 7 ).…”
Section: Discussionmentioning
confidence: 99%